Ionophoretic Activities of Phospholipids on Human Platelets - Ikeda, Yasuo; Kikuchi, Masao; Toyama, Keisuke; Watanabe, Kiyoaki; Ando, Yasuhiko (Thrombosis and Haemostasis, 1979)
The effects of phospholipids on calcium uptake by human platelets were investigated utilizing 45CaCl2. Among the phospholipids tested, cardiolipin and phosphatidic acid exerted a significant increase of calcium uptake by platelets. Calcium uptake was dependent upon cardiolipin concentration and incubation time. These phospholipids enhanced platelet aggregation induced by ADP (2 μM) or epinephrine (0.5 μg/ml). Cardiolipin caused the significant release of serotonin from platelets in the absence of externally added calcium in the medium.These results may suggest that phospholipids activate platelets through their ionophoretic activities.